Functional foods and intestinal homeostasis: The perspective of in vivo evidence. (May 2021) - Chen, Gang; Li, Yanwu; Li, Xuezheng; Zhou, Di; Wang, Yajun; Wen, Xiaoyan; Wang, Chengmin; Liu, Xinran; Feng, Yuan; Li, Bingxin; Li, Ning
Abstract: Background: The intestine is the well-acknowledged important organ where the nutritional molecules are absorbed. Meanwhile, intestinal ailments, including intestinal mucosal atrophy, barrier dysfunction (leaky gut), inflammation bowel disease (ulcerative colitis and Crohn's disease), irritable bowel syndrome (IBS), dysbacteriosis, and cancers (sporadic and colitis-associated intestinal cancers), have always been the top-ranking diseases that we are confronting. However, although there are several reports on the intestinal modulatory effects for the food macromolecular components (polysaccharides and prebiotics), the effects of low-molecular-weight phytochemicals from foods, especially those from functional foods, on intestinal ailments have not been methodically understood. Scope and approach: Various functional foods and their low-molecular-weight phytochemicals that help protect intestinal homeostasis have been demonstrated. The preliminary in vitro results are not included due to the uncertainty of their in vivo efficacy. This review compiles only in vivo bioactive reports and findings with solid pieces of evidence (both human and animal-based ones) to demonstrate the practical use of the food and its low-molecular-weight phytochemicals as complementary therapies or dietary supplements for intestinal health and their underlying mechanism of action. Key findings and conclusions: Functional foods (both the whole food and extracts) and their low-molecular-weight phytochemicals can benefit intestinal health of both small and large intestines at different stages of intestinal ailments through promoting intestinal epithelial renewal and barrier function, restoring intestinal flora, inhibiting intestinal inflammation and tumor growth, and exerting intestinal-cancer preventive effects. Therefore, depending on the circumstances of the intestinal ailment, intake of certain functional foods or their low-molecular-weight phytochemicals can relieve the symptom of intestinal ailments and contribute to the maintenance of intestinal homeostasis at different levels. Highlights: The effects of foods and their phytochemicals on intestinal homeostasis are summarized. Only clinical and in vivo results are compiled to assure the credibility of the conclusion in this paper. Recommendations are suggested with respect to different intestinal ailments.